Functions Whose Images are Terms of a Weakly Fixed Variable - Chortip Siwapornanan; Thodsaporn Kumduang; Junlouchai, Prapairat (Science & Technology Asia, 2025)
In this paper, the set of terms of a weakly fixed variable of type 𝜏 which is a generalization of terms of a fixed variable is introduced. Applying the generalized superposition operation, the superassociative algebra of terms of a weakly fixed variable is formed. Binary associative systems induced by such operations are obtained. We also discuss properties of functions whose images are terms of a weakly fixed variable called wfv-generalized hypersubstitions.